Natural population cohort study on long-lived adults: West China longevity and ageing procedure (WCLAP) - Li Wang; Yan Zhang; Qiukui Hao; Xiaoyan Chen; Birong Dong; Yan He; Meijuan Chen; Jirong Yue; Xiaochu Wu; Tianyao Zhang; Yan She; Yanling Gao; et al. (BMJ Open)
Purpose The West China longevity and ageing procedure (WCLAP) cohort study aims to provide guidance for older adults in western China with the aim of improving quality of life, reducing the burden of family care, summarising the characteristics of longevity lifestyles, building a Chinese-longevity-population biobank and exploring the mechanisms underlying population ageing.Participants Since the establishment of the WCLAP research baseline in 2018, a population of 1537 adults aged 80 years and above, living in the community, have been enrolled in the programme as research participants. Of these, 231 are aged 100 years and above. Participants are followed up every year.Finding to data WCLAP data are collected in five hospital research subcentres strategically located adjacent to the national ‘Longevity Townships’ of Chengdu Ziyang, Leshan, Yibin and Pengshan. Data collection included a comprehensive assessment of the participant’s health (including physical, psychological, social and common chronic disease assessments), instrumental tests (body composition and muscle percentage) and the collection of biomedical-biobank samples (include blood, urine, faeces, hair and urine).Future plans Through the annual cohort follow-up, survival-related information is collected at a group level. Analysis of biological samples facilitates biological characterisation at the microscopic level through proteomics, metabolomics, genomics and other techniques. Baseline data, group-level follow-up data and microbiological examination data are integrated together to provide an evaluation tool, exploring sarcopenia, disability, dementia, caregiver burden, ageing biomarkers and other influencing factors.Trial registration numbers 2018-463; ChiCTR1900020754.